When does curatively treated colorectal cancer recur? An Australian perspective. Issue 11 (2nd October 2018) - Reece, Mifanwy M.; Chapuis, Pierre H.; Keshava, Anil; Stewart, Peter; Suen, Michael; Rickard, Matthew J. F. X.
Abstract : Background: While most colorectal cancer (CRC) recurrences reportedly occur within 3 years following curative treatment, many studies are limited by short‐term follow‐up. This study examines the time to recurrence of CRC in a large Australian cohort with a long follow‐up period and assesses whether time to recurrence has changed over time. Methods: A comprehensive prospective database of patients undergoing resection for CRC is maintained at Concord Hospital, Sydney. Demographic and time to recurrence data were extracted for patients who developed a recurrence following potentially curative resection for colon cancer from 1995 to 2010 and rectal cancer from 1971 to 2010. Non‐deceased patients had a minimum of 5 years follow‐up. Results: Between 1995 and 2010, 2575 patients with CRC underwent surgery. After exclusions, 386 had recurrence following potentially curative resection, ranging from 1 to 172.5 months (median 20.3) after treatment. Within 1 year, 27.5% recurred, 57.5% by 2 years, 74.6% by 3 years, 85.5% by 4 years and 89.6% by 5 years. There was no difference in time to recurrence between colon and rectal cancers ( P  = 0.674). Among patients having a potentially curative resection for rectal cancer between 1971 and 2010, 386 recurred. There was no difference in time to recurrence by decade ( P  = 0.863). Conclusion: The majority of recurrences occurred within 3 years of curative treatment. Had surveillance been limited to 5 years, detection of more than 10% of recurrences would have been delayed. Time to recurrence for rectal cancer has not changed in over 40 years, despite treatment advances.